2021
DOI: 10.1071/pc20087
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Rāhui: placing Indigenous, conservation, and sustainability sciences in community-led conservation

Abstract: Resource sustainability requires recognising and developing pathways to integrate local and Indigenous knowledges alongside conservation and sustainability sciences within management practices and governance. However, knowledge never occurs in a vacuum, and is always mediated by the beliefs, values, or stances towards its possession or use within particular contexts. Focusing on the unprecedented renewal of a traditional practice of natural resource management in French Polynesia called rāhui, this article inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…In New Zealand, these achievements inform attempts by Māori to manage forest ecosystems and cultural keystone species. This movement is part of a more global trend towards community-led conservation, and one that places Indigenous communities at the centre (Palmer et al 2020;Fabre et al 2021). Moreover, recent research has demonstrated that employing good governance processes and managing social impacts may be more important than ecological effectiveness for maintaining local support for conservation (Bennett et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand, these achievements inform attempts by Māori to manage forest ecosystems and cultural keystone species. This movement is part of a more global trend towards community-led conservation, and one that places Indigenous communities at the centre (Palmer et al 2020;Fabre et al 2021). Moreover, recent research has demonstrated that employing good governance processes and managing social impacts may be more important than ecological effectiveness for maintaining local support for conservation (Bennett et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In French Polynesia the state has essentially used rāhui to rebuff Indigenous communities that have long used the concept to assert their own sovereignty. For the purposes of Western conservation it has also retooled this customary term to assert its own authority and legitimacy (as distinct from that of France) (Bambridge 2020;Fabre et al 2021). Here and elsewhere in the Pacific, however, the rationalized, scientific interpretation of endangered resources conflicts with the traditional, spiritual Indigenous relationship to land and resources represented by rāhui (Ruru and Wheen 2016).…”
Section: Spirits and Powermentioning
confidence: 99%
“…In the latter case, the decision to establish a large‐scale MMA encompassing its whole EEZ can be interpreted as an act of sovereignty in reaction to the growing influence of big conservationist NGOs functioning according to an enclave logic similar to mining and agribusiness corporations. The large‐scale MMA model seems to get growing attention in neighboring Pacific countries such as the Cook Islands and customary authorities are building extensive political networks across the Pacific Ocean while reviving the Polynesian concept of rāhui in their approach to marine governance (Bambridge 2016:2–4; who stresses the political dimension of the notion over its environmental dimension; see also Fabre et al 2021 and Dégremont this issue). In this respect Indigenous sovereign claims cannot be boiled down to local/infra‐state sovereignty as they enact broader transnational networks and rely on worldviews including human and non‐human actants such as the ocean itself which could be attributed legal personality if an ongoing initiative presented before the United Nations succeeds 13…”
Section: Postcolonial Turnsmentioning
confidence: 99%